The hypophagic factor oleoylethanolamide differentially increases c-fos expression in appetite regulating centres in the brain of wild type and histamine deficient mice. (November 2016) - Umehara, Hayato; Fabbri, Roberta; Provensi, Gustavo; Passani, M. Beatrice
Graphical abstract: Abstract: Histaminergic neurons in the hypothalamic tuberomamillary nucleus (TMN) establish connections with virtually all brain areas. Recent evidence suggests that feeding-related motivation is correlated with the activation of a subpopulation of histamine neurons in the ventral TMN that project to hypothalamic and subcortical areas controlling feeding behaviour. Oleoylethanolamide (OEA) is a hypophagic lipid-amide released by the small intestine in response to daily fat intake that indirectly activates hypothalamic oxytocin-neurons in the paraventricular (PVN) and supraoptic (SON) nuclei. We recently showed that OEA requires the integrity of neuronal histamine to fully display its hypophagic effect. Here we aimed to investigate if differences exist in OEA-induced c-Fos expression in several brain regions of fasted, histidine decarboxylase (HDC)-KO mice that do not synthesize histamine, and wild type (WT) littermates. All the brain regions examined receive histaminergic innervation and are involved in different aspects of feeding behaviour. We found that OEA increased c-Fos expression in the SON, arcuate nucleus (ARC) and the amygdala of WT mice, but not HDC-KO mice, whereas neither genotype nor treatment differences were observed in the lateral and dorsomedial hypothalamus. Furthermore, oxytocin-immunostaining was markedly increased in the neurohypophysis of WT and not in HDC-KO mice. Of note, OEA increased c-Fos expression in the nucleus of solitary tract of both genotypes. Our findings suggest that the TMN serves as a relay station to elaborate peripheral signals that control homeostatic and adaptive behavioural responses.